Effect of porphobilinogen on the formation of garlic green pigments. (21st February 2013) - Mou, Conghua; Hao, Xiaoran; Xu, Zhixiang; Qiao, Xuguang
Abstract: Background: Garlic ( Allium sativum L.) bulb is processed into various forms such as crushed garlic, garlic juice, granules, dehydrated garlic pieces and garlic powder. However, greening is often a major problem when garlic is crushed, since it affects the appearance and quality of the resulting product. Therefore study of the formation mechanism of garlic green pigments is very important for garlic processing . Results: The effect of porphobilinogen (PBG) on the formation of garlic green pigments was investigated in this study. As the storage time increased, there was a significant positive correlation between garlic greening and PBG content at low temperature (4 °C). PBG content decreased significantly during the garlic greening process. When treated with respiration inhibitor, both garlic greening strength and PBG content decreased as the concentration of respiration inhibitor increased. The green colour was generated when extracted PBG and allicin mixed thoroughly . Conclusion: There was a clear relationship between PBG content and garlic greening. As a provider of pyrrolyl compounds, PBG plays an important role in the formation of garlic green pigments. © 2013 Society of Chemical Industry